Evaluation of the Kirkpatrick Model Program at the Workshop on the Implementation of the Independent Curriculum of Luwu State Islamic High School - Zahir, Abdul; Masluddin, Masluddin (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study aims to evaluate the implementation of the Independent Curriculum Implementation Workshop (IKM) held at the Luwu State Islamic Senior High School (MAN Luwu). This study is an evaluation study with a mixed method approach using the Krikpatrick Model, where there are four levels measured, namely the reaction level, learning level, behavior level, and outcome level. Data in quantitative and qualitative forms were collected using questionnaires, interviews, observations, and documentation obtained from the Principal and Teachers of MAN Luwu which were then analyzed using descriptive quantitative (depicted numerically by displaying the amount and frequency of data) and descriptive qualitative (through the process of reduction, display, and drawing conclusions on data in the form of data, images, document, and behavior) data analysis techniques. The results of the study are that the IKM Workshop, in terms of implementation and implementation objectives, were achieved based on findings at four levels of evaluation. At the reaction level, workshop participants were satisfied with the implementation of the activity. Participants who attended the workshop gave very positive reactions. At the learning level, there was an increase in knowledge (cognitive) supported by an increase in participant skills in compiling IKM documents and a more positive attitude of participants after attending the workshop. At the behavioral level, there has been a change in participant behavior after attending the workshop, as evidenced by the implementation of IKM at MAN Luwu, which has run effectively. At the results level, this includes increasing production results, customer satisfaction in this case, the principal and students, increasing teacher morale, and creating positive alumni workshop relationships both within and outside the school environment, which have been implemented and achieved well.